Human induced pluripotent stem cell-derived cardiomyocytes as an electrophysiological model: Opportunities and challenges—The Hamburg perspective - Ismaili, Djemail; Schulz, Carl; Horváth, András; Koivumäki, Jussi T.; Mika, Delphine; Hansen, Arne; Eschenhagen, Thomas; Christ, Torsten (Frontiers in physiology, 2023)
Models based on human induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CM) are proposed in almost any field of physiology and pharmacology. The development of human induced pluripotent stem cell-derived cardiomyocytes is expected to become a step forward to increase the translational power of cardiovascular research. Importantly they should allow to study genetic effects on an electrophysiological background close to the human situation. However, biological and methodological issues revealed when human induced pluripotent stem cell-derived cardiomyocytes were used in experimental electrophysiology. We will discuss some of the challenges that should be considered when human induced pluripotent stem cell-derived cardiomyocytes will be used as a physiological model.